(untitled) (Conference on English Language Teaching, 2023)
Google form is one of technology that used to facilitate teachers and students in the learning process, especially in the assessment process. But in the reality when it was applied, there were some problems faced by the students about the usage of Google form. For this reason, the researcher is interested to explore the students’ perspective in issues of using Google form in English examination. This descriptive qualitative study examined how students perceived about the using Google form issue in English examination based on the students involved. A questionnaire with open-ended question was distributed as collective data. The participants are twenty five of ninth grade students of Islamic junior high school that place in one of village at Tanjung Pura, Langkat. There were four main conclusions from the study. They are; (1) Internet connection, (2) Low of students’ understanding in applying Google form, (3) Students’ dishonesty on English exam, (4) Lack of students’ exam media. Finally, the issues with using Google forms in English exams cannot be overstated because they have a big impact on the students’ grades and how well they learn the language.